PENERAPAN MIND MAPPING DALAM PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SMPN 9 KOTA JAMBI - Sri Dewi; Akhmad Faisal Hidayat (Universitas Batanghari Jambi, 2019)
Students' mathematical communication skills are still unsatisfactory, the average student error shows an error in expressing daily events in the language of mathematics. This is due to a lack of student understanding of the material that has been taught, and the level of students' creativity in recording important concepts contained in the content of the subject matter is still not satisfactory, student records tend to be still boring. The purpose of this study are: (1) to describe the implementation of mind mapping in the scientific approach to improve students' mathematical communication skills, and (2) describe the results of the assessment of mathematical communication skills that occur in students after learning is done with mind mapping in the scientific approach. The type of research that the author is doing is included in classroom action research (CAR). The author uses interview, observation, test and documentation methods. As for the analysis, the author uses descriptive qualitative analysis techniques, namely in the form of qualitative data and quantitative data that the author obtained during direct observation in the field. The research findings show that the application of mind mapping in the scientific approach can improve mathematical communication skills in students of Jambi City Vocational High School 9. (1) The process of implementing mind mapping with a scientific approach to improve students' mathematical communication skills can run smoothly as planned. The application of mind mapping has provided new experiences for students and teachers and provides several benefits, the benefits of mind mapping obtained include: students become the spirit of learning, students easily remember lessons and students gain drawing experience to find the relationship between one concept and another concept and the teacher easier to explain the subject matter to students; (2) on the assessment of students 'mathematical communication skills, from quantitative data the acquisition of scores on students' mathematical communication obtained a high enough value, namely in the first cycle the average value obtained was 75.87 or around 77.2%, in the second cycle there was an increase namely 80.1 or around 87.1%.Keywords: Mind Mapping, scientific approach, and mathematical communication skills